Scaffold fabrication via rapid prototyping - Fong, Ee Siang. (2009)
This project is designed to investigate the possibility of using a combination of methods to fabricate three dimensional tissue engineering scaffolds. The use of multiple techniques enables the final scaffold to have the advantages of both techniques and minimize the disadvantages of using just one technique to fabricate the scaffold. In this project Selective Laser Sintering (SLS) was used to fabricate the base scaffold while fibers were deposited on to the base scaffold using Electro Spinning of Polymeric Material. Poly-ε-Caporlactone (PCL) was used for both techniques due to its proven results in tissue engineering scaffolds. Base scaffold are made with sufficient rigidity and three dimensional structures to support the deposited fibers. The deposited fibers are then encapsulated within the base scaffold by using a gelatin solution of 10wt%. Other technique was also explored to build fixture to aid the alignment of the scaffolds during encapsulation stage. 3D Printing (3DP) was used to produce rigid reusable fixture to align the scaffolds. The short lead time and low cost of the 3DP technology also help to overcome some of the problem faced during the fabrication of the scaffolds.